Hyperacusis in migraine: pilot project - Maistro, Bruna; Machado, Ana Clara Oliver; Bossa, Beatriz Bagatim; Bello, Valéria Aparecida; Poli Frederico , Regina Célia; Silva, Aline Vitali da (Headache Medicine, 2022)
The stress caused by headache may be related to the development of hearing disorders, such as hyperacusis and phonophobia. Hyperacusis is an unpleasant sensation caused by exposure to a due reduction in your tolerance. Characterized by an increase in sound sensitivity via the auditory pathway and by the ability to hear. However, some few problems can occur, while others can even be from the intensity in case of elevation. Phonophobia is a common symptom and with migration criteria, without a diagnosis of hyperacusis was still little in this context. For this reason, a better understanding of hyperacusis corresponds to a new means for the management and diagnosis of migraine. Keywords: migraine, hyperacusis, phonophobia.